Robust real-time model predictive control for torsional vibration system - Boksuwan, Sungwan; Benjanarasuth, Taworn (My University, 2012)
In this paper, explicit, robust Model Predictive Control (MPC) is proposed for the control of a two-mass system in order to achieve not only good tracking performance and load-change effect rejection, but also low torsional vibration, when the measurement noise contains outliers. The control structure presented in this paper is based fundamentally on the combination of explicit MPC and region detection via a self-optimizing variable. In addition, the well-known Kalman filter is replaced by the robust Kalman filter to deal with the outlier signals. The effectiveness of the proposed method is compared with a PID-based control.
Keywords: Convex optimization; Embedded system; Explicit MPC; Kalman filter; Self-optimizing variable; Two-mass system